2021
DOI: 10.3390/ijms22137005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Porcine Pancreas Decellularization Conditions on the Quality of Obtained dECM

Abstract: Due to the limited number of organ donors, 3D printing of organs is a promising technique. Tissue engineering is increasingly using xenogeneic material for this purpose. This study was aimed at assessing the safety of decellularized porcine pancreas, together with the analysis of the risk of an undesirable immune response. We tested eight variants of the decellularization process. We determined the following impacts: rinsing agents (PBS/NH3·H2O), temperature conditions (4 °C/24 °C), and the grinding method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…On the contrary, Milan et al reported that SDC alone showed no success in retaining collagen, but in our study, it has retained the collagen on tissue edges (Milian et al, 2021). Besides this study, numerous other xenogeneic tissues have also exhibited superior results with TX-100, such as porcine aortic valves (GRAUSS et al, 2005), porcine pancreas (Klak et al, 2021;Zhu et al, 2021), and porcine liver (Mirmalek-Sani et al,…”
Section: Ihc Stainingcontrasting
confidence: 55%
See 2 more Smart Citations
“…On the contrary, Milan et al reported that SDC alone showed no success in retaining collagen, but in our study, it has retained the collagen on tissue edges (Milian et al, 2021). Besides this study, numerous other xenogeneic tissues have also exhibited superior results with TX-100, such as porcine aortic valves (GRAUSS et al, 2005), porcine pancreas (Klak et al, 2021;Zhu et al, 2021), and porcine liver (Mirmalek-Sani et al,…”
Section: Ihc Stainingcontrasting
confidence: 55%
“…On the contrary, Milan et al reported that SDC alone showed no success in retaining collagen, but in our study, it has retained the collagen on tissue edges ( Milian et al, 2021 ). Besides this study, numerous other xenogeneic tissues have also exhibited superior results with TX-100, such as porcine aortic valves ( GRAUSS et al, 2005 ), porcine pancreas ( Klak et al, 2021 ; Zhu et al, 2021 ), and porcine liver ( Mirmalek-Sani et al, 2013 ), etc. Whereas in other investigations, SDS has been favored over TX-100 for decellularization of densely fibrous tissues such as kidney and liver, as TX-100 has demonstrated poor outcomes ( Hussein et al, 2016 ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…TX100 remove GAGs and decreases laminin and fibronectin content, but it does not affect collagens, showing its detrimental effects on ECM are milder than their ionic counterparts [75,84]. Moreover, considerable research indicates TX100 is cytotoxic, necessitating TX100-derived ECM safety control before clinical translation [85]. Retention of TX100 within dECM should be minimized by applying lower concentrations and different washing steps to achieve scaffolds with less than 15mM remaining TX100 concentrations, which was previously shown to get tolerated well by human cell lines [86].…”
Section: Chemical and Biological Agentsmentioning
confidence: 99%
“…This method was confirmed to clear cells and myelin sheaths effectively, and the yielded allografts achieved good nerve regeneration after transplantation. 18 Although nonionic detergent Triton X‐100 is described to cause minimal damage to the native tissues, 19 SDC, an ionic detergent, is considered to be one of the most potent and disruptive chemical agents. Subsequently, Hudson et al proposed a milder chemical treatment consisting of several steps repeated twice as well.…”
Section: Introductionmentioning
confidence: 99%